Dampak Media Sosial bagi Kehidupan Perkawinan di Ponorogo - Zulfi Rifqi Izza; Miftahul Huda (Journal of Economics, Law, and Humanities, 2022)
Information technology, especially social media, is one of the advances in information and communication. The growing number of social media allows information to spread easily in the community. With the development of technology in the household breakdown. This paper aims at the impact of the use of social media on married life in Ponorogo Regency, causing divorce. In accordance with these objectives, the data studied uses conflict theory, which is how the community manages the conflicts they experience can be resolved or not, resulting in divorce. This study uses a qualitative approach through field research based on data collected through interviews and observations. This study reveals a result of the impact of this s ocial media is the incident of an affair and online gambling. The statement that they are using this social media with their own selfishness, with this social media with any freedom. The impact is really real on third parties and some are using it as an online gambling medium.